An estimation of CPI biases in Argentina 1985-2005 and its implications on real income growth and income distribution - Pablo Gluzmann; Federico Sturzenegger (Latin American Economic Review, 2018)
We use the shifts in Engel curves calculated from household surveys to estimate CPI biases in Argentina between 1985 and 2005. We find that real earning levels increased during this period between 4.3 and 5.7% faster per year than previously estimated. More surprisingly, relative to conventional wisdom, that income distribution has improved throughout this period.
Keywords: N1; O47; 330; Argentina; GDP growth; Engel Curve; CPI Bias